Periodicity estimation of Dynamic Textures. (24th March 2009) - Bijon, Khalid Zaman; Hasan, Ahmed; Rahman, Ashfaqur; Murshed, Manzur
Dynamic Textures (DTs) are image sequences of natural events like fire, smoke, water etc., that possesses regular motion patterns. Periodicity is a widely used tool to analyse regular structures of periodic one dimensional signals as well as two dimensional image textures. In this paper we present a technique to compute periodicity of regular motion patterns of DT. The proposed technique is based on co-occurrence matrix calculation – another commonly used tool in image texture analysis. Experimental results demonstrate the ability of the proposed technique to categorise the DT in terms of their periodicity and achieving good classification results using computed periods.